Screening of Klebsiella pneumoniae subsp. pneumoniae Strains with Multi-Drug Resistance and Virulence Profiles Isolated from an Italian Hospital between 2020 and 2023 - Valentina Dimartino; Carolina Venditti; Francesco Messina; Silvia D'Arezzo; Marina Selleri; Ornella Butera; Carla Nisii; Alessandra Marani; Alessia Arcangeli; Roberta Gaziano; Terenzio Cosio; Pietro Scanzano; et al. (MDPI AG, 2024)
Klebsiella pneumoniae strains that are resistant to multiple drugs (KPMDRs), which are often acquired in hospital settings and lead to healthcare-associated infections, pose a serious public health threat, as does hypervirulent K. pneumoniae (hvKp), which can also cause serious infections in otherwise healthy individuals. The widespread and often unnecessary use of antibiotics seen during the recent COVID-19 pandemic has exacerbated the challenges posed by antibiotic resistance in clinical settings. There is growing concern that hypervirulent (hvKp) strains may acquire genes that confer antimicrobial resistance, thus combining an MDR profile with their increased ability to spread to multiple body sites, causing difficult-to-treat infections. This study aimed to compare resistance and virulence profiles in KPC-3-producing K. pneumoniae isolates collected over four years (2020-2023). A genome-based surveillance of all MDR CRE-K. pneumoniae was used to identify genetic differences and to characterize the virulence and resistance profiles. Our results provide a picture of the evolution of resistance and virulence genes and contribute to avoiding the possible spread of isolates with characteristics of multi-drug resistance and increased virulence, which are thought to be one of the main global challenges to public health, within our hospital.